DESIGN, OPTIMIZATION AND EVALUATION OF CETRIZINE DIHYDROCHLORIDE FAST DISSOLVING FILMS EMPLOYING STARCH TARTRATE–A NOVEL SUPERDISINTEGRANT - KUMAR, R. SANTOSH; KUMARI, ANNU; LATHA, B. KUSUMA; RAJ, PRUDHVI (International Journal of Current Pharmaceutical Research, 2019)
Objective: The aim of the current research is optimization, preparation and evaluation of starch tartrate (novel super disintegrant) and preparation of fast dissolving oral films of cetirizine dihydrochloride by employing starch tartrate. Methods: To check the drug excipient compatibility studies of the selected drug (Cetrizine dihydrochloride) and the prepared excipient i. e starch tartrate, different studies like FTIR (Fourier-transform infrared spectroscopy), DSC (Differential scanning calorimetry) and thin-layer chromatography (TLC) were carried out to find out whether there is any interaction between cetirizine dihydrochloride and starch tartrate. The solvent casting method was used for the preparation of fast dissolving films. The prepared films were then evaluated for thickness, folding endurance, content uniformity, tensile strength, percent elongation, in vitro disintegration time and in-vitro dissolution studies. Response surface plots and contour plots were also plotted to know the individual and combined effect of starch tartrate (A), croscarmellose sodium (B) and crospovidone (C) on disintegration time and drug dissolution efficiency in 10 min (dependent variables). Results: Films of all the formulations are of good quality, smooth and elegant by appearance. Drug content (100±5%), thickness (0.059 mm to 0.061 mm), the weight of films varies from 51.33 to 58.06 mg, folding endurance (52 to 67 times), tensile strength (10.25 to 12.08 N/mm2). Fast dissolving films were found to disintegrate between 34 to 69 sec. Percent dissolved in 5 min were found to be more in F1 formulation which confirms that starch tartrate was effective at 1%. Conclusion: From the research conducted, it was proved that starch tartrate can be used in the formulation of fast dissolving films of cetirizine dihydrochloride. The disintegration time of the films was increased with increase in concentration of super disintegrant.